Ultrasound measurements as evidence for the use of stretch shortening cycle in diagonal skiing - Komi, P.; Ishikawa, M.; Linnamo, V. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
Stretch-shortening cycle (SSC) type muscle actions are typical in most sport activities, and visible even to the naked eye in such cases as jumping, hopping, running and throwing. In hopping, for example, SSC refers by definition to lengthening (stretch) of the active muscles followed immediately by shortening in the push-off phase of the leg extensors (e.g. Komi, 1983). The basis for the use of SSC instead of pure concentric muscle actions is simple: the neuromuscular system makes an effort to perform the movement as efficiently as possible. In SSC the active stretching (eccentric) phase allows storage of elastic energy which can be utilized partly in the subsequent shortening (concentric) phase. The centrally controlled preactivation combined with the active eccentric phase prepares the muscle to receive the "impact" and store this elastic energy. When these conditions (preactivation and active stretching phase) were met, Komi and Norman (1987) were able to suggest - with the use of combination of kinematic, electromyographic (EMG) as well as ski and pole force measurements - the existence of SSC in diagonal technique cross-country (x-c) skiing. However, this observation could not be confirmed until the high speed ultrasonographic (US) method had developed so that it could be utilized also in field testing. The present study was able to use this new US technology for the first time in x-c skiing. The specific purpose of the study was to examine simultaneously the behavior of muscle-tendon unit (MTU) and muscle fascicles during diagonal technique x-c skiing.